Prescribing trends in respiratory tract infections in a tertiary care teaching hospital - Beg, Mirza A.; Dutta, Shakti B.; Bawa, Shalu; Kaur, Amanjot; Vishal, Subhash; Kumar, Upendra (International Journal of Research in Medical Sciences, 2017)
Background: Respiratory tract infections are a major cause of morbidity and mortality in developing countries. Polypharmacy and irrational prescribing in respiratory diseases are common practice worldwide. Keeping in consideration this scenario, present study was undertaken to analyze the drug utilization pattern of respiratory tract infections. Methods: This drug utilization study was conducted by Pharmacology department at SGRRIM & HS to analyze drug utilization pattern of respiratory infections. A total of 585 prescriptions were collected from hospital and randomly evaluated for prescribing pattern using WHO drug indicators. Results: A total of 585 prescriptions were analyzed. Male:Female ratio was 1:0.77. Age wise distribution was done; 81(13.84%) 0-15 years, 54(9.23%) 16-30 years, 198(33.84%) 31-45 years, 75(12.82%) 46-60 years and 177(30.25%) patients belongs to >60 years of age group respectively. A total of 4869 drugs were prescribed, 2754(56.56%) antibiotics, 675(13.8%) bronchodilators, 630(12.93%) corticosteroids, 303(6.22%) antacids, 507(10.41%) in miscellaneous category respectively. 2562(52.61%) oral, 1491(30.62%) injectable and 816(16.75%) inhalational drugs were prescribed. Numbers of Fixed dose combinations were 645(13.24%). 8.32 drugs were prescribed per prescription. 2409(49.47%) drugs were prescribed from national essential medicine list 2015. 4320(88.72%) drugs were prescribed by their brand names. Conclusions: Irrational prescribing and polypharmacy was observed. The drug utilization studies are important tool to sensitize and increases awareness among physicians, which ultimately improves rational prescribing and patient care.